L'impact de qualité de l'air intérieur en milieu résidentiel sur la santé respiratoire - Norman King (VertigO)
Over the past twenty years, several epidemiological studies have shown that the prevalence of asthma has risen dramatically in North America and Europe. Several authors suggest that this increase is at least partly due to an increased exposure to indoor air contaminants in the residential environment. In this article, we will present some data an the prevalence of asthma and then discuss the different indoor air contaminants that can cause or aggravate this disease and other respiratory problems. Preventive methods will be briefly discussed.